(untitled) (Світ фінансів, 2017)
Дишкант О. В. Організація та завдання державного фінансового контролю в управлінні видатками бюджету. Розкрито організацію та завдання державного фінансового контролю в управлінні видатками державного бюджету. Систематизовано організаційні норми, форми контролю та суб’єкти його здійснення. Розглянуто бачення провідних науковців та практиків на місце, роль та значення державного контролю у державному управлінні. Проаналізовано недоліки здійснення державного фінансового контролю в управлінні видатками державного бюджету. Запропоновано та узагальнено напрямки удосконалення контрольно-ревізійного процесу в управлінні видатками державного бюджету. Дышкант О. В. Организация и задачи госсударственного финансового контроля в управлении расходов бюджета. Раскрыто организацию и задачи государственного финансового контроля в управлении расходами государственного бюджета. Систематизированы организационные нормы, формы контроля и субъектов его осуществления. Рассмотрено точку зрения ведущих ученых и практиков на место, роль и значение государственного контроля в государственном управлении. Проанализированы недостатки осуществления государственного финансового контроля в управлении расходами государственного бюджета. Предложено и обобщенно направления совершенствования контрольно-ревизионного процесса в управлении расходами государственного бюджета. Dyshkant O. Organization and objectives of public financial management control in expenditure budget. Introduction: complexity of the modern state’s development require an acceleration of reforming the entire state-management system. Purpose: The analysis and a generalization of the organization and objectives of the public financial control, justification of recommendations for improving the control and auditing process in the management of public expenditure. Results: Market conditions do not cancel the need for regular monitoring of financial and economic activity of enterprises, institutions and organizations, for taking the appropriate measures to prevent and to eliminate weaknesses and violations of the law. Conclusion: 1. Creation system of a financial control associated with the development and adoption of the fundamental law “On financial control in Ukraine”; 2. The role of the coordinator with the right to make final decisions on controversial issues should be assigned to one of the control services; 3. It is important to change the range and character of controls measures that are fulfilled by the Accounting Chamber; 4. The implementation of the audit of the financial and budgetary reporting is reasonable; 5. The submitting of Financial Statements together with the audit report of the Accounting Chamber.